2017
DOI: 10.18632/oncotarget.20458
|View full text |Cite
|
Sign up to set email alerts
|

miR-93-3p inhibition suppresses clear cell renal cell carcinoma proliferation, metastasis and invasion

Abstract: miRNA dysregulation is associated with many human diseases, including cancer. This study explored the effects of miR-93-3p on clear cell renal cell carcinoma (ccRCC). We found that miR-93-3p is upregulated an average of 38-fold in 138 ccRCC specimens compared to matched normal kidney tissues, which correlated with poor patient outcome. miR-93-3p inhibition reduced ccRCC cell growth, invasion, and migration in vitro and in a mouse xenograft model. A search of the TargetScan, miRanda, and PicTar databases reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Anticancer ZNF238 is repressed by miR‐20b overexpression whereas ZNF24, a tumor promoter, is increased by miR‐940 dysregulation (Lu et al , ). In clear cell renal cell carcinoma cells, miR‐93‐3p was found to decrease the expression of pigment epithelium‐derived factor (PEDF) and inhibit osteogenesis (Wang et al , ). As a single miRNA can distinctively alter the expression of multiple mRNA transcripts (Hu et al , ; Li et al , ), we hypothesized that miR‐93‐3p dysregulation is closely related to CC cell behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticancer ZNF238 is repressed by miR‐20b overexpression whereas ZNF24, a tumor promoter, is increased by miR‐940 dysregulation (Lu et al , ). In clear cell renal cell carcinoma cells, miR‐93‐3p was found to decrease the expression of pigment epithelium‐derived factor (PEDF) and inhibit osteogenesis (Wang et al , ). As a single miRNA can distinctively alter the expression of multiple mRNA transcripts (Hu et al , ; Li et al , ), we hypothesized that miR‐93‐3p dysregulation is closely related to CC cell behavior.…”
Section: Discussionmentioning
confidence: 99%
“…As a class of small noncoding RNAs, microRNAs (miRNAs) play significant roles in post‐transcriptional gene regulation by targeting the 3′UTR of target messenger RNAs (mRNAs) and decreasing the stability and/or translation of these mRNAs (Bei et al , ). MiRNA dysregulation and its effects have been observed in a variety of human diseases, and various miRNAs can function as potential candidates for CC treatment and prognosis (Liang et al , ; Wang et al , ; Zhou et al , ). In particular, miR‐93 is reported to be involved in CC metastasis and invasion (Wang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Separately, 11 studies from eight articles 15,[56][57][58][59][60][61][62] were included in the diagnostic meta-analysis and 14 studies from 13 articles 15,24,29,41,47,51,[63][64][65][66][67][68][69] were included in the prognostic meta-analysis. After screening the titles and abstracts, 476 articles were excluded because they were reviews (n = 18), meta-analyses (n = 5), nonhuman studies (n = 14), or studies irrelevant to our topic (n = 439).…”
Section: The Basic Characteristic Of Meta-analysismentioning
confidence: 99%
“…miRNAs regulate RNA degradation or translation by binding to target mRNA 3′‐UTR at the posttranscriptional level . A number of studies have shown that several miRNAs act as oncogenes in ccRCC, including miR‐566, miR‐93, miR‐195, and miR‐429 . miR‐452 is also upregulated and acts as an oncogene in several cancers .…”
Section: Discussionmentioning
confidence: 99%